Danaparoid use for haemodialysis in a morbidly obese patient with heparin-induced thrombocytopenia – Need for a higher than recommended weight-based dosing. Issue 180 (August 2019) - Castelino, Ronald L.; Maddula, Meghana; Tarafdar, Surjit; Sud, Kamal; Kairaitis, Lukas
Summary: What is known and objective: Heparin is widely used to prevent clotting of the extracorporeal circuit during haemodialysis (HD). Heparin-induced thrombocytopenia (HIT) is a potentially devastating immune mediated adverse drug reaction caused by the emergence of antibodies that activate platelets in the presence of heparin, leading to a pro-thrombotic state. Danaparoid is an alternative anticoagulant used in patients on HD with HIT but its dosing recommendations in obese patients on HD are relatively scarce. Case summary: We report a case of a 48-year-old morbidly obese patient who received weight-based dosing of danaparoid for HD with monitoring of anti-Xa activity. However, despite the patient's anti-Xa level being within the therapeutic range at various time points, the circuit lines kept clotting during HD. What is new and conclusion: The report provides evidence that the manufacturer's recommendations on dosing danaparoid based on body weight may lead to sub-optimal therapeutic benefit and highlight the need for higher than recommended weight-based dosing in obese individuals on dialysis.